2020
DOI: 10.1101/2020.05.31.20118745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 trend in Bangladesh: deviation from epidemiological model and critical analysis of the possible factors

Abstract: Background: Since its first report on March 08, COVID-19 positive cases and number of deaths are increasing in Bangladesh. In the first month of COVID-19 infection, incidence of daily positive cases did follow the susceptible, infected and recovered (SIR) based predictions we reported in April, but started to deviate in the following months. COVID-19 transmission and disease progression depends on multifaceted determinants e.g. viral genetics, host immunity, social distancing, co-morbidity, socio-demographic a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Their findings suggest that early growth of COVID-19 cases followed an exponential pattern with an estimated 5.16 days doubling period. A recent study [ 14 ] reported that the COVID-19 trend in Bangladesh showed deviation from the epidemiological model, and they identified potential factors responsible for this deviation. Overall, Bangladesh’s COVID-19 characteristic patterns reflect the following: an inadequate testing and treatment capacity, insufficient supply of personal protection equipment, poor public sanitation practices, poorly managed public health care system and services, lack of public awareness, large-scale violation of social distancing order ( Figure 1 , Figure 3, Figure A2 and Figure A3 ), a large vulnerable population (e.g., Rohingya refugees), community-level transmission, and dire economic impacts [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings suggest that early growth of COVID-19 cases followed an exponential pattern with an estimated 5.16 days doubling period. A recent study [ 14 ] reported that the COVID-19 trend in Bangladesh showed deviation from the epidemiological model, and they identified potential factors responsible for this deviation. Overall, Bangladesh’s COVID-19 characteristic patterns reflect the following: an inadequate testing and treatment capacity, insufficient supply of personal protection equipment, poor public sanitation practices, poorly managed public health care system and services, lack of public awareness, large-scale violation of social distancing order ( Figure 1 , Figure 3, Figure A2 and Figure A3 ), a large vulnerable population (e.g., Rohingya refugees), community-level transmission, and dire economic impacts [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…That means the number of people tested positive is dependent on the number of tests. It should be mentioned here that the number of tests per day has also declined since the fourth month of the pandemic due to people’s dwindling interest resulting from various aspects, such as social stigma, fear, long queue, and waiting time in sample collection, delayed in providing test results, and introducing fees for tests [ 3 ]. It should be noted that Bangladesh is ranked 15 th globally in terms of the total number of COVID-19 positive cases while 157 th in terms of tests per million population (as on 25 September 2020) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive hassle of travel, the inability to get a suitable web-based slot or the long queue at the testing site might have limited their access for a regular check-up. 12 …”
Section: Discussionmentioning
confidence: 99%